Strategi Pemasaran Perusahaan Starbucks Terhadap Penurunan Saham Akibat Boikot Produk - Erwin Permana; Dhea Novtalia Wijaya; Lutfita Khoirunisa; Samsyurizal (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
Starbucks is one of the international coffee companies affected by falling shares due to a boycott triggered by their alleged support for alleged Israeli crimes. To overcome this market turmoil, Starbucks is trying to carry out a series of strategies so that it can still be accepted by the market. This research aims to analyze Starbucks' marketing strategy regarding the decline in shares due to product boycotts. The research was conducted using a descriptive qualitative approach. Data was obtained through search results and observations on various sites and related databases. The research results show that Starbucks has implemented a marketing strategy that focuses on clarifying its stance and commitment to human values, launching aggressive promotions, launching new products, collaborating with K-Pop idols, improving customer service, and taking advantage of the Ramadan momentum. In addition, Starbucks has also emphasized its dedication to social responsibility and human rights through statements on Starbucks' official website and Instagram. The company is concerned about all forms of actions that incite hatred and violence, and also expresses sympathy for the victims and support for global peace initiatives. These efforts aim to restore Starbucks' brand image and rebuild customer trust, while addressing the concerns that led to the product boycott. By focusing on these human values, promotions, and improving customer service, Starbucks is working to regain its market position and continue to grow in the international coffee industry